2004
DOI: 10.1097/01.asn.0000118529.01681.4f
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Lead and Progression of Chronic Renal Diseases

Abstract: Abstract. Previous retrospective research suggests that lowlevel environmental lead exposure is associated with an acceleration of age-related impairment of renal function. For elucidating the long-term relationship between low-level environmental lead exposure and progression of chronic renal diseases in patients without diabetes, 121 patients who had chronic renal insufficiency, a normal body lead burden (BLB), and no history of exposure to lead were observed prospectively for 48 mo. Associations of both BLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 30 publications
8
89
1
1
Order By: Relevance
“…The observations suggestive of a relationship between PbB and decrements in glomerular filtration rate derived from the studies presented in Table 3-3 are consistent with those of a smaller prospective clinical study in which progression of renal insufficiency was related to higher lead body burden among patients whose PbB was <15 μg/dL (Lin et al 2001;Yu et al 2004). Mean PbB in a high lead body burden group (EDTA provocation test yielded >600 μg excreted/72 hours) were 6.6 μg/dL (range, 1.0-15 μg/dL) compared to 3.9 μg/dL (1-7.9 μg/dL) in a low body burden group.…”
Section: Health Effectssupporting
confidence: 77%
“…The observations suggestive of a relationship between PbB and decrements in glomerular filtration rate derived from the studies presented in Table 3-3 are consistent with those of a smaller prospective clinical study in which progression of renal insufficiency was related to higher lead body burden among patients whose PbB was <15 μg/dL (Lin et al 2001;Yu et al 2004). Mean PbB in a high lead body burden group (EDTA provocation test yielded >600 μg excreted/72 hours) were 6.6 μg/dL (range, 1.0-15 μg/dL) compared to 3.9 μg/dL (1-7.9 μg/dL) in a low body burden group.…”
Section: Health Effectssupporting
confidence: 77%
“…The relation of lead burden to progression was confirmed in a prospective study, which documented that doubling of serum creatinine or end-stage renal disease was seen more frequently in patients with high-normal as opposed to low body lead burden (25) when assessed by the ethylene diaminotetraacetic acid (EDTA) mobilization test (24). The role of lead is made even more convincing by a further study in chronic kidney disease (CKD) patients: In a first observational phase a higher body lead burden was identified as a predictor of the rate of loss of GFR; in a subsequent phase patients with a high-normal body lead burden were randomized to receive at regular intervals placebo or infusions of calcium disodium EDTA.…”
mentioning
confidence: 70%
“…In the current study, the lead levels in all the house dust samples (including the work area samples) were approximately 1/250 of the EPA standard of 40 µg/929 cm 2 surface area. 13 However, Yu et al 14 reported that low-level environmental lead exposure was associated with accelerated deterioration of renal insufficiency in patients with initial chronic renal disease, no history of occupational lead exposure, and blood lead levels far below the normal range. Mercury concentrations in house dust, although very low, were significantly higher in surface dust samples collected in jewelry-making compared with control homes.…”
Section: Discussionmentioning
confidence: 99%